The neuropsychiatric sequelae of mercury poisoning. The Mad Hatter's disease revisited. - O'Carroll, R; Masterton, G; Dougall, N; Ebmeier, K; Goodwin, G (1995)
BACKGROUND: The detailed effects of mercury poisoning on cognitive function, brain anatomy and regional brain function are largely unknown. We report the case of a 38-year-old man who was exposed to toxic levels of inorganic mercury. METHOD: Four years after exposure, the patient was assessed using magnetic resonance imaging (MRI), single-photon emission computerised tomography (SPECT) and detailed neuropsychological evaluation. RESULTS: The patient developed a myriad of physical and psychiatric complaints, including stomatitis, muscle spasm, tremor, skin rash and the psychiatric syndrome known as 'erythism' (Mad Hatter's disease). Neuropsychological evaluation revealed marked and significant deficits of attention concentration, particularly when under time pressure. The MRI scan was unremarkable; however, SPECT revealed hypermetabolism of the posterior cingulate CONCLUSIONS: Mercury poisoning appeared to result in a dysregulation of posterior cingulate cortex, which was associated with attention/concentration deficits and marked anxiety/agitation.